Rechtliche Aspekte des Einsatzes von KI in der Medizin, insbesondere Regulierung und Arzthaftung = Legal Aspects of the Use of AI in Medicine, in Particular Regulation and Medical Liability - Eichelberger, Jan (Zeitschrift für medizinische Ethik, 2025)
The use of Artificial Intelligence in medicine raises a number of legal issues from a wide variety of perspectives, in addition to medical, ethical, and social issues. This article focuses on two areas. The first concerns the regulation of AI through the Artificial Intelligence Regulation (AI Act) and its interaction with the Medical Devices Regulation. The second discusses key aspects of medical liability when using AI in medicine., AbstractThe use of Artificial Intelligence in medicine raises a number of legal issues from a wide variety of perspectives, in addition to medical, ethical, and social issues. This article focuses on two areas. The first concerns the regulation of AI through the Artificial Intelligence Regulation (AI Act) and its interaction with the Medical Devices Regulation. The second discusses key aspects of medical liability when using AI in medicine.